Design and implementation of an open source transmission line impedance matching educational framework - (:unkn) unknown (WILEY, 2020)
Determining input impedance, assigning reflection coefficient, and matching load impedance are important transmission line problems those involve complex calculation steps because of complex connection architectures in transmission lines. Efficient understanding of such problems in undergraduate and graduate courses should be supported by rich visualization tools. The Smith chart is a convenient tool for transmission line calculations especially for wave propagation and maximum power theory that discusses impedance matching problems. In this context, we can say that Java is a widely used open source educational tool having strong computational environment for research and development aims. In this study, an open source transmission line impedance matching educational framework (TLIME) has been designed to teach efficiently wave propagation and maximum power theory that discusses the impedance matching problems. The success of developed educational framework has been measured by a questionnaire held in courses in the third and fourth years of the electrical and electronics engineering undergraduate program at Sakarya University of Applied Sciences, Turkey. The visual preparation of the problem solutions with rich graphical user interface and simulations of the mathematical representations has been evaluated to contribute to a better understanding of the wave propagation and impedance matching transmission line subjects. The functionality and simplicity of the developed framework scored by over 82% among course enrolled students. The rest of the paper is organized as follows. Section 2 explains transmission line impedance matching problem in the context of maximum power theory. Section 3 discusses transmission line planning and problem solving with Smith chart. Section 4 discusses explanation and usage of developed TLIME framework and last section discusses results.
Keywords: educational framework; impedance matching problems; java programming; Smith chart; transmission line; wave propagation theory